Experiential festival attributes, perceived value, satisfaction, and behavioral intention for Korean festivalgoers. (April 2019) - Lee, Hoon; Hwang, Heejeong; Shim, Changsup
Based on an extensive literature review of the festival experience, this study proposes that the experiences of festivalgoers can be classified into five main attributes, namely Escape, Playfulness, Togetherness, Sacredness, and Placeness. A survey of 450 South Koreans who had participated in some type of domestic festival in the past year statistically validated these attributes and explored the impact of each on the perceived value, satisfaction, and behavioral intentions of festivalgoers. The study shows that those Koreans who experienced Playfulness, Sacredness, and Placeness at a festival tended to perceive the festival as more valuable than those who experienced Escape and Togetherness, which were factors that did not significantly affect the perceived value of the festival. This study illuminates the nature of festival attributes and the particular characteristics most important to Korean festivalgoers, both of which provide theoretical and practical implications for tourism researchers and festival organizers.